Formulaic Expressions in Kadınhanı (Konya) Dialect - Kılıç, Fatma (Fırat University, 2025)
Structures such as formulaic words, idioms, and proverbs are frequently encountered in the vocabulary. These structures, which become patterns over time through repetition, are passed down from generation to generation. Apart from the formulaic words used in the standard language, the formulaic words used in Anatolian dialects also enrich the language with their diversity. Recording these structures, which are passed down from generation to generation through oral heritage, in written form is of great importance in terms of the historical course of the Turkish language. While studies on formulaic words, which are a reflection of cultural richness just like proverbs and idioms, are increasing, the need for comprehensive studies that address the subject in detail continues. This study was based on the classification of formulaic words found in the master's thesis titled "Kadınhanı Dialect". Formulaic words identified in the Kadınhanı Dialect were examined under fifteen headings based on their meanings, such as those indicating separation, farewell, those indicating religious beliefs, those indicating emotional reactions, those indicating criticism and warning, those indicating welcome, those indicating folk beliefs, those indicating asking after someone's well-being, etc. This study, in which a total of 113 formulaic words were identified, will contribute to language studies.

Söz varlığı içerisinde kalıp söz, deyim, atasözü gibi yapılara sıkça rastlanır. Zamanla tekrar ede ede birer kalıp hâlini alan bu yapılar kuşaktan kuşağa aktarılır. Ölçünlü dilde kullanılan kalıp sözler dışında Anadolu ağızlarında kullanılan kalıp sözler de çeşitliliğiyle dile zenginlik katar. Nesilden nesile sözlü miras yoluyla aktarılan bu yapıların yazılı olarak kayıt altına alınması Türk dilinin tarihî seyri açısından büyük önem taşımaktadır. Tıpkı atasözleri ve deyimler gibi kültürel zenginliğin birer yansıması olan kalıp sözler üzerine çalışmalar çoğalmakla birlikte konuyu detaylı olarak ele alan kapsamlı çalışmalara duyulan ihtiyaç devam etmektedir Bu çalışma “Kadınhanı ağzı” adlı yüksek lisans tezinde bulunan kalıp sözlerin tasnifi üzerine oluşturulmuştur. Kadınhanı ağzında tespit edilen kalıp sözler anlamlarına göre kavram alanı esas alınarak ayrılık, vedalaşma bildirenler, dini inançları bildirenler, duygusal tepkileri bildirenler, eleştiri ve uyarı bildirenler, karşılama bildirenler, halk inanışlarını bildirenler, hatır sorma bildirenler vb. şeklinde on beş başlık altında incelenmiştir. Toplamda 113 kalıp sözün tepit edildiği bu çalışma dil çalışmalarına katkı sağlayacaktır.
Kadınhanı (Konya) Ağzında Kalıp Sözler
Keywords: Linguistic Structures (Incl. Phonology; Morphology and Syntax); Dilsel Yapılar (Fonoloji; Morfoloji ve Sözdizimi dahil)